Genetic Diversity of CD14 Promoter Gene Polymorphism (rs2569190) is Associated With Regulation of Malaria Parasitemia and Susceptibility to Plasmodium falciparum Infection. (16th August 2017) - Ojurongbe, Olusola; Funwei, Roland I; Snyder, Tara J; Aziz, Najihah; Li, Yi; Falade, Catherine O.; Thomas, Bolaji N
CD14 is a multifunctional receptor expressed on many cell types and has been shown to mediate immune response resulting in the activation of an inflammatory cascade, with polymorphism of its promoter (rs2569190) found to be associated with susceptibility to several diseases. In malaria infection, the CD14 gene demonstrated a pathogenic profile in regulating experimental cerebral malaria, with reports of elevated levels of soluble CD14 in serum of patients but no definitive conclusion. We present a detailed analysis of genetic diversity of CD14 promoter gene (snp −159 C/T; rs2519190) polymorphism between a malaria-infected group and uninfected controls and its association with clinical parameters of disease. Genomic DNA samples obtained from 106 Plasmodium falciparum malaria–infected patients and 277 uninfected controls were elucidated with a polymerase chain reaction-restriction fragment length polymorphism (RFLP) assay. Our results show a significant diversity ( P = 3.32E−06) in the genotypic frequency (3.8% versus 22.4%) of the rs2569190 mutant variant between the malaria-infected group and controls, respectively. The mutant allele had the lowest frequency among the malaria-infected group demonstrating its necessity for infection. Mean parasitemia (parasites/μL of blood) was significantly regulated based on CD14 polymorphic profile (19 855 versus 37 041 versus 49 396 for homozygote mutants, heterozygotes, and homozygote wild type, respectively). Interestingly, we found no association between CD14 genetic variants with fever, age of patients, or anemia. How this affects disease severity between subregional and continental groups deserves further clarification, including extending these studies in a larger group and among severe and asymptomatic patients with malaria.